IMPLICATIONS AND EFFICACY OF THE INDIAN MULTI-STATE COOPERATIVE SOCIETY AMENDMENT ACT 2023: A COMPREHENSIVE ANALYSIS - Subramanian, Ramana (International Journal of Cooperative Law, 2024)
The Multi-State Cooperative Society Amendment Act 2023is a significant milestone in the evolution of India’s cooperative sector. The Act aims to address governance deficiencies and enhance cooperation among cooperatives in India. One notable example is the Act’s establishment of the Cooperative Rehabilitation, Reconstruction, and Development Fund to revive ailing multi-state cooperative societies. This initiative aims to support struggling cooperatives. However, it also imposes a financial burden on profitable entities. Requiring profitable cooperatives to contribute to the fund may raise questions about equity and competitiveness within the sector. The Act also introduces measures to promote democratic governance, including the establishment of the Cooperative Election Authority, Information Officer, and Ombudsman. These initiatives aim to enhance transparency, accountability, and member participation in cooperative decision-making processes, to foster a more inclusive and responsible cooperative environment. However, challenges persist, particularly regardingthe balance between central and state government jurisdiction over cooperative governance. Disputes over legislative competency and potential encroachments on state autonomy underscore the need for nuanced approaches to cooperative regulation that respectboth principles of federalism and cooperative principles. This paper evaluates the implications and efficacy of the Act, focusing on key provisions and their potential impact on cooperative governance, financial sustainability, and overall sectoral development.